Liquid-phase exfoliation of graphite into graphene nanosheets in a hydrocavitating 'lab-on-a-chip'. Issue 6 (24th January 2019) - Qiu, Xiaoyu; Bouchiat, Vincent; Colombet, Damien; Ayela, Frederic
Abstract : Graphene nanosheets were exfoliated from hydrodynamic cavitation performed inside a microchannel. Abstract : Hydrodynamic cavitation 'on a chip' has been used to achieve liquid-phase exfoliation of natural graphite to get graphene. We have taken advantage of the small size of such a 'lab-on-a-chip' (LOC) with low input-power consumption, to produce afterwards few layers of graphene nanosheets in a surfactant suspension. Characterization of the processed material has been performed by TGA analysis, SEM, TEM, AFM and Raman measurements. Observations have demonstrated the presence of monolayers and few layers of graphene with a lateral size around 300 nm, exfoliated from a graphite powder suspension flowing through the microsystem.